Low association between bleeding on probing propensity and the salivary aMMP‐8 levels in adolescents with gingivitis and stage I periodontitis. (11th December 2020) - Räisänen, Ismo T.; Sorsa, Timo; Tervahartiala, Taina; Raivisto, Teija; Heikkinen, Anna Maria
Abstract: Background and Objective: Bleeding on probing (BOP) is a widely accepted measure used in periodontal diagnostics. Previous studies suggest that several factors can affect BOP propensity. The aim of this study was to investigate the relative impact of different local and modifying factors on BOP levels. Materials and Methods: The oral health of five hundred and forty‐four adolescents (two birth cohorts) aged 15‐17 years living in Kotka, Finland, was examined including periodontal probing depth, visible plaque index, root calculus, and BOP. Whole saliva samples were collected and measured for active matrix metalloproteinase‐8 (aMMP‐8) by time‐resolved immunofluorometric assay (IFMA). Results: Bacterial plaque/calculus accumulation (oral hygiene) had a major influence on BOP levels. The relative impact was several times greater compared with the extent of periodontal pocketing, aMMP‐8 levels, smoking, toothbrushing, or gender. Furthermore, BOP levels were significantly elevated among adolescents with poor oral hygiene than good oral hygiene even if adjusted for the extent of periodontal pocketing ( P  < .001). BOP levels could be low even if several ≥ 4 mm deep periodontal pockets existed. The difference in the extent of periodontal pocketing was not significant between the two birth cohorts of adolescents ( P  = .731). Conclusions: BOP levels can be regarded as an important indicator of the extent of bacterial challenge and its adverse effects on the gingival inflammation. However, the level of oral hygiene may mask the association between the extent of gingival bleeding and the severity of the periodontal inflammatory condition. Thus, relying on BOP levels (below 10% or 20%) may provide insufficient information about the periodontal treatment need of an adolescent depending on his/her level of oral hygiene. Yet, more research is needed to confirm the results, also in adult populations.